Design and Development of a Novel Humidex based Air Conditioner Controller - Kumar, Abhishek (My University, 2007)
In present era, to maintain certain level of physical comfort, use of air conditioner is becoming more and more popular. However conventional air conditioners are not energy efficient as they operate mostly described by a band of temperature limits. Human comfort, on the other hand is dependent not only on temperature but also on relative humidity i.e. at the same temperature say 300, if humidity is low, discomfort is less as compared to if humidity is high. To incorporate this factor of humidity, an index known as humidex was proposed [“http://www.wul.qc.ec.gc.ca/meteo/documentation/Humidex/humidex_a.html”] and operating air conditioners in the prescribed humidex zone is not only more comfortable but also economical. The present work revolves around microcontroller based intelligent air conditioning control system that takes inputs in the form of temperature and humidity, computes the humidex and gives user a choice to operate in “comfort” or “economy” mode.
Keywords: Humidex Operation; Air Conditioner Controller